Analysis of Social Communication Skills in Experimental PGSD’ Students: A Case Study at a University - Ribka Yago; Nurhasanah; Arpiani; Yulia Astuti (Madako Elementary School, 2025)
PGSD students of Madako Tolitoli University generally still experience obstacles in communicating effectively, especially in their social environment. This is a crucial challenge in the process of forming their communication skills as prospective educators in elementary schools. This study aims to analyze the effectiveness of the strategy of developing students' communication skills in the social context of experimentation as a learning strategy in improving students' communication skills. This study uses an experimental contextual study method, which analyzes the impact of implementing real-life based strategies. Data collection techniques include observation, in-depth interviews, and documentation. The research subjects consisted of five students in the sixth semester of PGSD Madako Tolitoli University who were selected purposively. The results of this study show that students' communication skills in the experimental social context are applied with the strategy of open thematic discussion forums (87.88%), social interaction simulations (83.66%), and collaborative studies across study programs (84.21%). The results of each of these findings had a good impact on improving students' communication skills after they were involved in social experiment activities. Contributively, these findings can be used as an alternative learning strategy that is effective in developing the communication skills of PGSD students at Madako Tolitoli University.